School Shootings and Suicide: A Comparison of School Shooters Who Die by Suicide and Non-Suicide School Shooters - Sanders, Kaelyn (Crime & delinquency, 2025)
This study comparatively examines whether suicide school shooters differ from non-suicide school shooters. Although the research on school shootings is increasing, there is limited research on school shooters who attempt, threaten, or plan suicide or die by suicide in comparison to those who do not. The American School Shooting Study (TASSS) includes data on all school shooting events occurring in the United States between 1990 and 2016 that resulted in at least one injury. This study extracts event and individual characteristics from TASSS to quantitatively explore which attributes explain differences across these groups. We conclude by discussing recommendations on responding to school shootings and highlighting directions for future research.